Linguistic features of Malaysian students’ online communicative language in an academic setting: the case of Universiti Kebangsaan Malaysia - Fuzirah Hashim,; Ahmad Aminuddin Soopar,; Bahiyah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Social media have gained astounding worldwide growth and popularity and have become prominent in the life of many young people today. According to various research studies in the field of online social networks, social media sites such as Facebook, Twitter and Whatsapp are greatly impacting the lives of youths. These sites have provided a platform whereby the young can create groups based on their common interests and build connections by updating various topics to discuss. However, with social media taking up such a large space in our lives, there is a concern as to whether it is impacting our communicative language; more importantly, our youth’s communicative language. In view of this phenomenon, this article is an attempt to add to the understanding of online communicative language used by youths in social media. Specifically, it reports on the linguistic features of online communicative language used by youths in an academic setting in Facebook. This study employed two research tools, namely Virtual Ethnography and Content Analysis. Data collected was in the form of screen captures and snippets of conversations. Content Analysis was employed to look into the occurrences of languages in contact in phenomena such as code-mixing, code-switching and borrowings of certain words from the first language-second language and vice versa. The findings of the study indicate that the language used by the participants on Facebook consists of a mixture of code-switching, code-mixing, fillers, emoticons, spelling modifications, foreign language words and colloquial Malaysian English.